Overexpression of an mRNA dependent on rare codons inhibits protein synthesis and cell growth. - Zahn, K (1996)
lambda's int gene contains an unusually high frequency of the rare arginine codons AGA and AGG, as well as dual rare Arg codons at three positions. Related work has demonstrated that Int protein expression depends on the rare AGA tRNA. Strong transcription of the int mRNA with a highly efficient ribosome-binding site leads to inhibition of Int protein synthesis, alteration of the overall pattern of cellular protein synthesis, and cell death. Synthesis or stability of int and ampicillin resistance mRNAs is not affected, although a portion of the untranslated int mRNA appears to be modified in a site-specific fashion. These phenotypes are not due to a toxic effect of the int gene product and can be largely reversed by supplementation of the AGA tRNA in cells which bear plasmids expressing the T4 AGA tRNA gene. This indicates that depletion of the rare Arg tRNA due to ribosome stalling at multiple AGA and AGG codons on the overexpressed int mRNA underlies all of these phenomena. It is hypothesized that int mRNA's effects on protein synthesis and cell viability relate to phenomena involved in lambda phage induction and excision.